2003
DOI: 10.1103/physrevb.67.012407
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioelectron theory for magnetism in Fe:  Pressure dependence of spin-wave energies, exchange parameters, and Curie temperature

Abstract: The spin-wave spectra for bcc Fe at various lattice constants are calculated by the ab initio density functional electron theory for various lattice constants, and the exchange parameters of a Heisenberg model are determined from the data. The spin-wave energies increase with decreasing lattice constant, and the behavior of the exchange parameters can by no means be described by the Bethe-Slater curve for an effective nearest-neighbor Heisenberg model. From the spin-wave frequencies the pressure dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 27 publications
4
37
1
Order By: Relevance
“…7͑a͒, we plot J ij ef f as functions of the lattice constant from the 1NN to the ninth NN. 53 however, there is no cross over between J 1 ef f and J 2 ef f in our GGA results.…”
Section: Resultscontrasting
confidence: 45%
“…7͑a͒, we plot J ij ef f as functions of the lattice constant from the 1NN to the ninth NN. 53 however, there is no cross over between J 1 ef f and J 2 ef f in our GGA results.…”
Section: Resultscontrasting
confidence: 45%
“…Leger and Loriers-Susse (1972) reported the independence of T c and stress; they showed that the magnetic phase transition remained at a given temperature, even when under stress. However, Morán et al (2003) produced inconsistent results, concluding that the Heisenberg model might not correctly describe this phenomenon. Later, Körmann et al (2009) reported good consistency between their calculated and experimental results.…”
Section: Introductionmentioning
confidence: 90%
“…Theoretically, Morán et al (2003) and Körmann et al (2009) used nearly identical methodologies, but obtained different results. Both calculated T c by integrating magnon energy along a high symmetry path in the Brillouin zone (the so-called 'frozen magnon' approach) (Halilov et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Fe, they show very good agreement with experimental Curie temperatures. The exchange interactions are strongly simplified, assuming a 1/r 3 functional dependence obtained from fitting two sets of calculated exchange integrals [3,23]. These exchange integrals are truncated to second-nearest neighbors, and do not take into account the detailed and oscillatory behavior of the exchange further out, which is relevant in many different magnetic materials.…”
Section: Introductionmentioning
confidence: 99%